Management and treatment decisions in progressive pulmonary fibrosis - Lipsi, Roberto; Baglioni, Stefano; Eslami, Amir; Dodaj, Meridiana (Rassegna di Patologia dell'Apparato Respiratorio, 2024)
Background. Interstitial lung diseases (ILDs) include about 200 different, chronic, pathological entities characterized by similar clinical features. The development of interstitial fibrosis, during the course of these diseases is considered a common, unpredictable, irreversible and self-sustaining mechanism of progression with decline of pulmonary function and respiratory symptoms till death. In recent years many efforts and attention have been made by scientists bringing to definition of the “progressive phenotype” that can be considered as “a disease inside the disease” with similar genetic, pathological and clinical characteristic regardless of the initial fibrotic pathology. Objective. In this review, we have explored the state of the art and the most recent literature around progressive pulmonary fibrosis (PPF); definition, early detection, molecular basis and therapy. Methods. We searched papers published in English language on PubMed using the keywords: “interstitial lung disease”, “progressive pulmonary fibrosis”, “idiopathic pulmonary fibrosis”, “pirfenidone”, “nintedanib”. Results. Since the initial therapy must be set according the underlying desease, antifibrotic drugs (nintedanib and pirfenidone), initially indicated only to slow the progression in Idiopathic pulmonary fibrosis (IPF) have been recently considered effective to slow the progression in other ILDs. Conclusion. It is extremely important to recognize early the PPF by means of physiological and radiological follow-up. Currently, no serum biomarkers are available for monitoring or predict disease progression so, we need more randomized clinical trial to better investigate the hallmarks of progression and the effects of antifibrotic drugs to modify prognosis of these patients.